2016
DOI: 10.1264/jsme2.me16074
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Structures in Freshwater Polar Environments of Svalbard

Abstract: Two thirds of Svalbard archipelago islands in the High Arctic are permanently covered with glacial ice and snow. Polar bacterial communities in the southern part of Svalbard were characterized using an amplicon sequencing approach. A total of 52,928 pyrosequencing reads were analyzed in order to reveal bacterial community structures in stream and lake surface water samples from the Fuglebekken and Revvatnet basins of southern Svalbard. Depending on the samples examined, bacterial communities at a higher taxono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…An interesting parallel can be made between our microbial mats and two oligotrophic microbial mats from the investigation conducted by Bonilla-Rosso et al (2012). In the study of microbial mats in oligotrophic ponds, Bonilla-Rosso et al (2012) speculated that the microbial mat from the oligotrophic desiccation pond would have higher diversity than expected for such environment, & Cowan, 2014;Glöckner et al, 2003;Ntougias et al, 2016). Recent studies also identified some members of phylum Planctomycetes as colonizers of extreme acidic environments (Fuerst & Sagulenko, 2013).…”
Section: Extreme Events Shifting Mat Community Structurementioning
confidence: 64%
See 1 more Smart Citation
“…An interesting parallel can be made between our microbial mats and two oligotrophic microbial mats from the investigation conducted by Bonilla-Rosso et al (2012). In the study of microbial mats in oligotrophic ponds, Bonilla-Rosso et al (2012) speculated that the microbial mat from the oligotrophic desiccation pond would have higher diversity than expected for such environment, & Cowan, 2014;Glöckner et al, 2003;Ntougias et al, 2016). Recent studies also identified some members of phylum Planctomycetes as colonizers of extreme acidic environments (Fuerst & Sagulenko, 2013).…”
Section: Extreme Events Shifting Mat Community Structurementioning
confidence: 64%
“…In addition, candidate phyla TM6 and SM2F11, as well as bacteria from the genera Shewanella (Gammaproteobacteria) and Pirellula (Planctomycetes) were exclusively enriched in this extreme winter conditions. Species of SM2F11, Shewanella and Pirellula, were previously identified in different extreme cold environments for which they evolved a number of adaptive strategies with the aim to maintain vital cellular functions in conditions of cold, desiccation, radiation, excessive UV radiation and temperature, and low nutrient availability (De Maayer, Anderson, Cary, & Cowan, ; Glöckner et al, 2003; Ntougias et al, ). Recent studies also identified some members of phylum Planctomycetes as colonizers of extreme acidic environments (Fuerst & Sagulenko, ).…”
Section: Discussionmentioning
confidence: 99%
“…The average amino acid identity (AAI) within coherent phylogenomic groups was determined by performing whole-genome pairwise CDSs comparisons, using BLAST software, as previously described by Konstantinidis and Tiedje [29]. Taxonomic categories for the MAGs where defined using the standards suggested by Konstantinidis et al [30].…”
Section: Supplementary Materials and Methodsmentioning
confidence: 99%
“…In spite of their initial description in freshwater environments [2, 7], the majority of ecological and genomic studies were performed on marine ecosystems and seawater isolates [16, 18, 23, 29]. Although they represent one of the major prokaryotic groups in freshwater (with highly variable abundances from <1% up to 22%) [27, 3032] and have been shown to have major roles in dissolved organic matter fractionation [33], our understanding of Planctomycetes is based on data derived largely from culture-based approaches [2, 34, 35], short reads analyses or/and hybridization-based techniques [27, 31, 32, 36]. While prone to primer coverage biases [37], the 16S rRNA gene-based studies pointed out that the abundant freshwater ribotypes do not have counterparts in culture and that their genomic diversity and ecological significance remains elusive [27, 32, 38].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the experimental procedure, imaging of the desired amplification products was performed in a Gel Doc™ XR+ system (Bio-Rad) after loading 5 μl from each PCR reaction on 1.5% (w/v) agarose gels and separating them by electrophoresis. Purification of the PCR products was carried out with a 20% PEG, 2.5 M NaCl solution as previously described [113]. The concentration of purified PCR product was measured with a Quawell Q5000 micro-volume UV-Vis spectrophotometer.…”
Section: Sample Purification and Sanger Sequencingmentioning
confidence: 99%